Adaptive Concurrent Medium Access Control for Wireless Mesh Network - Ibrahim, Mohd Sufiz; Ahmad, Mohd Riduan; Gannapathy, Vigneswara Rao (2010)
This paper proposes an adaptive concurrent transmission protocol implemented in Wireless Mesh Network (WMN), which reduces the overhead due to signalling of the existing concurrent transmission protocols such as Medium Access Control (MAC) protocol with Acknowledgment and Parallel mechanism (MACA-P), Concurrent MAC with Short Signalling (CMAC-SS) and Distribution Coordination Function (DCF). DFC protocol is widely used and implemented in the existing IEEE 802.11b/g/n standard wireless networks. The use of DCF in WMN reduces the throughput per hop significantly due to exposed node avoidance mechanism such as Ready-to-Send and Clear-to-Send (RTS-CTS) signalling which allows only one transaction per node at one time; meaning that the waiting delay is higher in Wireless Mesh Network (WMN). MACA-P and CMAC-SS protocols introduce concurrent transmission mechanism that allows multiple transactions per hop at one time. The results from the simulation show that the performance of CMAC-SS is better than the MACA-P. However the design of both MACA-P and CMAC-SS considers fixed size of signalling which makes the protocol not scalable when the number of user within the network increases. In order to provide scalability, an adaptive size of signalling is introduced in this paper by manipulating the broadcast nature of the wireless network within the slotted framework. Such adaptive mechanism improves scalability and also the throughput per hop by 45% compared to CMAC-SS when the number of nodes is higher than 10.